The shackling of people with mental disorders in the light of the encyclical Fratelli Tutti - Bour, Eugenius Koresy; Ndepong, Bertolomeus (Institut Agama Kristen Negeri Toraja, 2025)
Shackling is still often used as a solution to address issues affecting people with mental disorders (PMD) in Sikka Regency. This study aims to discuss and explain the reality of shackling of PMD in Sikka Regency as a practice of ‘culture of throwing away’ based on the principles outlined in the Encyclical Fratelli Tutti. This research uses a mixed method. The research result shows that people with mental disorders (PMD) are one of the groups that are vulnerable to becoming victims of the culture of throwing away. The manifestation of the culture of throwing away towards the PMD can be seen in the act of shackling. The Encyclical Fratelli Tutti emphatically emphasizes the inherent dignity of every individual and demands full respect for the dignity of all people, including the most vulnerable. According to the Encyclical Fratelli Tutti, the shackling of PMD constitutes an act of violence that tarnishes the sanctity of life and violates human rights. It also manifests egoism and individualism. The shackling of PMD also leads to the breakdown of the family’s proximity relationship. The solution to facing the globalization of indifference, according to Pope Francis, is repentance by living a culture of solidarity, like the example of the Good Samaritan (Luke 10:25-37). Thus, the practice of shackling PMD in Sikka Regency reflects the ‘culture of throwing away’ criticized by the Encyclical Fratelli Tutti, which emphasizes the importance of respect for human dignity.